Between Economic Exploitation and Economic Nationalism: European Exporting Firms and African Merchants in the Cocoa Pool Crisis of 1937-1938 in Nigeria - Alimi, Shina (African historical review, 2025)
This article is a re-examination of the cocoa pool crisis in Nigeria between 1937 and 1938. Existing studies have largely focused on the activities of European exporting firms while treating the roles of African middlemen in passing. Beyond the dominant skewed analysis in literature, this article provides a holistic view of the cocoa pool crisis of 1937-1938. It raises important ethical questions around the trading strategies of European exporting firms in Africa and the indigenous African merchants, largely dominated by the educated elite. It also situates the 1937-1938 cocoa pool crisis within the scope of the colonial exploitative economy in which both European and African merchants played their respective roles. I argue that like the European exporting firms, the marketing strategies adopted by African middlemen were characteristically exploitative. New evidence shows that although both European exporting firms and African middlemen clothed their activities in a benign protective gesture towards the illiterate cocoa farmers, the crisis revealed correspondence of interests between the Colonial Office in London and the produce exporting firms in Nigeria. It also created much doubt about the benign motives of African merchants towards cocoa farmers. Although the involvement of some educated elites gave the protest a nationalistic appeal, it became clear that the crisis was motivated by the clash of economic interests between African middlemen and European exporting firms. Thus, this crisis represented the height of economic conflicts and struggles between European firms and African merchants on the eve of the Second World War.